Reading note on the book "Globalisation and Communication Technologies in Africa" - (:unkn) unknown (My University, 2005)
Adorned with the virtues of progress, the new information technologies (NITs) appear to be indispensable for access to world markets in the context of globalisation, where interconnection is now a system. On the African continent, NITs are gradually being integrated into the economic fabric and social relations along the sometimes tortuous paths of development.
Keywords: African Research